2013
DOI: 10.1001/jamadermatol.2013.4413
|View full text |Cite
|
Sign up to set email alerts
|

A Vascular Growth Following Radiation Therapy for Breast Carcinoma Treatment

Abstract: A woman in her 70s presented with an asymptomatic erythematous papule of unknown duration on the right breast. Four years previously, shehadbeentreatedforductalcarcinomainsituoftherightbreastwith alumpectomyandradiationtherapy.Thephysicalexaminationrevealed numerous telangiectasias involving the right breast and an erythematous vascular papule on the superior lateral right breast (Figure, A). A shave biopsy of the lesion was performed (Figure, B and C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Furthermore, the effect of surgery itself was highlighted by Yoon and colleagues, who observed that the radicality of surgery was more predictive of subsequent development of AVLC than tumor stage 18 . Lastly, several recent studies also suggested radiotherapy as an etiology in the development of AVLC 31,32 . Radiation likely induces inflammatory changes and tissue fibrosis, which compromises lymphatic drainage 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the effect of surgery itself was highlighted by Yoon and colleagues, who observed that the radicality of surgery was more predictive of subsequent development of AVLC than tumor stage 18 . Lastly, several recent studies also suggested radiotherapy as an etiology in the development of AVLC 31,32 . Radiation likely induces inflammatory changes and tissue fibrosis, which compromises lymphatic drainage 33 .…”
Section: Discussionmentioning
confidence: 99%
“…18 Lastly, several recent studies also suggested radiotherapy as an etiology in the development of AVLC. 31,32 Radiation likely induces inflammatory changes and tissue fibrosis, which compromises lymphatic drainage. 33 The overwhelming majority (91.4%) of patients in the current study received radiation, which seems to support this notion.…”
Section: Discussionmentioning
confidence: 99%